Alternative Legal Strategies and Ninik Mamak Authority: Dual Administration of Malay Marriage in Koto Kampar Hulu, Riau - Mustafid, Mustafid; Gemilang, Kemas Muhammad; Putra, Firman Surya; Al Bajuri, Azzuhri; Mawardi, Mawardi (Journal of Islamic Law, 2024)
The regulation of marriage registration in several Muslim countries tends to emphasize administrative aspects rather than substantive ones. For the Malay customary community in Koto Kampar Hulu, Riau, Indonesia, their obligations are not only limited to fulfilling marriage administration under state law but also involve obtaining permission from ninik mamak (traditional leader). Therefore, this article aims to analyze marriage administration in the context of customary law and state law within the Malay customary community, as well as to reveal alternative legal strategies they employ to circumvent traditional marriage administration. Field research was conducted through interviews with 16 key informants and direct observation of the completeness of marriage administration. The results show that the Malay customary community must navigate dual marriage administrations—customary law and state law—to obtain the legality of marriage before the state. Permission from ninik mamak serves as the basis for acquiring documents from the village head, fulfilling the administrative requirements for marriage registration at the local religious affairs office. The authority of ninik mamak in granting marriage permission aims to resolve conflicts and customary obligations before marriage while preserving the identity and traditions of the customary community. For those who disregard customary administration, they adopt alternative legal strategies such as unregistered marriages (nikah sirri) or relocating to another village. The alignment between customary law and state law is reflected in this study, particularly in the context of marriage registration. [Regulasi pencatatan perkawinan di beberapa negara Muslim cenderung menekankan aspek administratif daripada substansial. Bagi komunitas Adat Melayu di Koto Kampar Hulu, Riau, Indonesia, kewajiban mereka tidak hanya terbatas pada pemenuhan administrasi perkawinan dalam hukum negara, tetapi juga melibatkan proses mendapatkan izin dari ninik mamak (tokoh adat). Oleh karena itu, artikel ini bertujuan untuk menganalisis administrasi perkawinan dalam konteks hukum adat dan hukum negara di kalangan komunitas Adat Melayu, serta mengungkap strategi hukum alternatif yang mereka terapkan untuk mengelabui administrasi perkawinan adat. Penelitian lapangan dilakukan melalui wawancara dengan 16 informan kunci dan observasi langsung terhadap kelengkapan administrasi perkawinan. Hasil penelitian menunjukkan bahwa komunitas Adat Melayu harus mengatasi administrasi perkawinan ganda, yaitu hukum adat dan hukum negara, guna mendapatkan legalitas perkawinan di hadapan negara. Izin dari ninik mamak menjadi dasar untuk memperoleh dokumen-dokumen dari kepala desa, persyaratan administratif untuk pencatatan perkawinan di kantor urusan agama setempat. Otoritas ninik mamak dalam pemberian izin perkawinan bertujuan untuk menyelesaikan konflik dan tanggungan adat sebelum perkawinan, sambil melestarikan identitas dan tradisi masyarakat adat. Bagi masyarakat yang mengabaikan administrasi adat, mereka mengadopsi strategi hukum alternatif seperti perkawinan siri atau pindah domisili ke desa lain. Keselarasan antara hukum adat dan hukum negara tercermin dalam studi ini, khususnya dalam konteks pencatatan perkawinan.]